Legal Implications and Urgency Of Changing Ordinary Delicates Into Complaint Delicates In Copyright Law Number 28 Year 2014 - Jubaidi, Didi; Khoirunnisa, Khoirunnisa (Indonesian Scientific Publication, 2024)
The change of the ordinary offense to a complaint offense in Copyright Law Number 28 of 2014 has significant legal implications and emphasizes the importance of adjusting the law to protect copyright. This change reflects the need to adapt the law to current realities and demonstrates a commitment to international standards and the interests of copyright holders. However, effective enforcement of these changes faces challenges in identifying and dealing with copyright infringement, which requires collaborative efforts and continuous legal updates. This research aims to analyze the legal implications and urgency of the change from ordinary offense to complaint offense related to Copyright Law (UUHC) Number 28 of 2014. The results show that treating copyright infringement as a complaint offense (klach delict) can lead to difficulties in law enforcement and an increase in copyright infringement in Indonesia. This is because the authorities cannot take direct action unless there is a complaint first from the injured party, as a result it can have a negative impact on the creative industry and make creators less motivated. This can have a negative impact on the creative industry and make creators less motivated to create original works. In addition, the consequence could be a decrease in tax revenue received by the government.